1925 Nev. Stat. 54, ch. 47, § 2 - (:unkn) unknown (General Publisher, 1925)
Prohibited noncitizens and convicts from owning, possessing, or having under their custody or control any pistol, revolver, or concealable firearms; violators subject to felony conviction and imprisonment of 1-5 yrs.
--
Keywords: POSSESSION - DANGEROUS PERSONS